Temporal Trends in the Incidence and Disability Adjusted Life Years of Schizophrenia in China Over 30 Years - Dong, Wanyue; Liu, Yunning; Sun, Jianzhong; Liu, Yan; Sun, Zhonghe; Bai, Ruhai (Frontiers in Psychiatry, 2022)
Background: Schizophrenia is an important public health problem in China. This study aims to assess the long-term trends in the incidence and disability-adjusted life years (DALYs) rate of schizophrenia in China between 1990 and 2019. Methods: The incidence and DALYs data were drawn from the Global Burden of Disease Study 2019, and an age–period–cohort model was used in the analysis. Results: The age-standardized incidence rate (ASIR) and age-standardized DALYs rate (ASDR) of schizophrenia increased by 0.3% and 3.7% for both sexes between 1990 and 2019. For males, the local drift for incidence was higher than 0 (P<0.05) in those aged 10 to 29 years (local drifts, 0.01% to 0.26%) and lower than 0 (P<0.05) in those aged 35 to 74 years (local drifts, -1.01% to -0.06%). For females, the local drift was higher than 0 (P<0.05) in those aged 10 to 34 years (local drifts, 0.05% to 0.26%) and lower than 0 (P<0.05) in those aged 40 to 74 years (local drifts, -0.86% to -0.11%). The local drift for DALYs rate was higher than 0 (significance with P<0.05) in the age group from 10 to 69 years (local drifts, 0.06% to 0.26 for males and 0.06 to 0.28 for females). The estimated period and cohort relative risks (RR) for DALYs rate of schizophrenia were found in monotonic upward patterns, and the cohort RR for the incidence increased as the birth cohort moved forward starting with those born in 1972. Conclusions: Although the crude incidence of schizophrenia has decreased in China, the ASIR, ASDR, and crude DALYs rate all showed a general increasing trend over the last three decades. The DALYs rate continue to increase as the birth cohort moved forward, and the increasing trend of incidence was also found in individuals born after 1972. More efforts are needed to promote mental health in China.